Changes in Peyer’s Patch and Cecal Tonsil B Lymphocytes in Laying Hens Following Challenge with Salmonella enterica Serovar Enteritidis - Holt, Peter S.; Vaughn, Lara E.; Gast, Richard K. (International Journal of Poultry Science, 2011)
Two trials were conducted to determine B cell changes in Peyer’s Patches (PP) and Cecal Tonsils (CT) of specific-pathogen-free Single Comb White Leghorn hens challenged with Salmonella enterica Serovar Enteritidis (SE). Prior to challenge and then weekly post challenge, 4 or 3 hens in Trials 1 and 2, respectively, were sacrificed and their intestinal tracts excised. Cells were purified from proximal and distal PP along with both CT and then aliquots of cells were incubated with antibodies to chicken immunoglobulins IgM, IgG and IgA. The B cells expressing the different immunoglobulin isotopes were identified via flow cytometric analysis. B lymphocytes expressing IgM were most prevalent, representing 40-60% and 30-50% of CT and PP B cells, respectively, while 20-30% of CT and PP lymphocytes expressed IgA. Only a small percentage of CT and PP lymphocytes, <10%, expressed IgG. Significantly more IgM+ cells were detected in CT vs proximal and distal PP and proximal PP in trials 1 and 2, respectively. Significantly more IgA+ cells were observed in proximal PP vs distal PP and CT in trial 1 but not in trial 2. Following SE infection, these differences were no longer observed. For IgG+ cells, however, no significant differences between tissues were observed prior to challenge but significantly more IgG+ cells were observed in both PP vs CT at weeks 1 and 3 post challenge in trial 1 and week 1 post challenge in trial 2. These results indicate that B lymphocyte differences do occur in PP vs CT in adult chickens and these populations can change in response to stimuli such as intestinal infection.